Digitale Praktiken und das Studium - Steinhardt, Isabel (Entwicklungen im Feld der Hochschule)
Anhand einer explorativen Studie in den Fächern Jura und Soziale Arbeit wird rekonstruiert welche Praktiken Studierende in Bezug auf digitale Technologien haben und ob digitale Praktiken im Studium existieren. Dazu wurden narrative Interviews mit sechs Studierenden geführt, die habitushermeneutisch ausgewertet wurden. Die Ergebnisse zeigen keine digitalen Praktiken in Bezug auf das Studium, wohingegen sich digitale Praktiken im alltäglichen Leben zeigen. Für das Studium zeigen sich unterschiedliche Praktiken in der Nutzung digitaler Technologien, die in Beziehung zu den Kapitalsorten stehen, die Studierende besitzen. Die explorativen Ergebnisse legen nahe, dass Studierende unterschiedliche Hilfestellungen in Bezug auf die Digitalisierung des Studiums benötigen, die in der Lehrplanung und -pädagogik berücksichtigt werden müssten.

Hochschulinnenpolitik. Mikropolitische Verhältnisse der Hochschuldidaktik - Steinhardt, Isabel (Handbuch Hochschuldidaktik)
Die Hochschuldidaktik wurde in den letzten zehn Jahren flächendeckend an deutschen Hochschulen ausgebaut, da die Qualität der Lehre als Faktor im nationalen wie auch internationalen Wettbewerb der Hochschulen angesehen wird. In diesem Beitrag wird untersucht, wie sich dieser Ausbau mikropolitisch in der Arena Hochschule niederschlägt. Hierzu wurden eine systematische Literaturauswahl durchgeführt und mittels qualitativer Inhaltsanalyse einschlägige Texte der Hochschuldidaktiker:innen analysiert. Für die theoriegeleitete qualitative Inhaltsanalyse wurden als deduktive Kategorien die von Crozier und Friedberg (1993) benannten Machtquellen Expertise, Kommunikations- und Informationsflüsse, organisationale Regeln und Umweltkontakte verwendet. Fazit der Untersuchung ist, dass die Hochschuldidaktik zwar viele Stellen hinzugewonnen hat, es allerdings kaum einen Zuwachs an Macht gab, der nun in die Entscheidungs- und Aushandlungsprozesse innerhalb der Hochschulen eingebracht werden könnte.
Keywords: Mikropolitik; Macht; Machtquellen; Positionseffekte; Hochschuldidaktik

Permanent provisionality: The homes of mobile managerial professionals between temporariness and permanence - Spiegel, Anna (Transitions: Journal of Transient Migration)
Nowadays, mobility and transience are no longer exclusively associated with the marginalized and socially excluded, such as homeless or displaced people. On the contrary, mobility and transience have become a constitutive pattern of the highly skilled postmodern workforce. Yet, how mobile professionals negotiate the meaning of their homes in âliquid timesâ and what homemaking practices they use to deal with the temporal uncertainty of their homes are questions that still require further research. This article â based on ethnographic research on German and American managers conducted in China, Germany and the United States between 2011 and 2014 â contributes to this research question by examining how mobile professionals make sense of the transience of their current homes and how transience is reflected in their homemaking practices. The article argues that for mobile professionals the home becomes a critical place not only because of new multilocal spatialities but also because of new transient temporalities. Due to the corporate practice of giving successive temporary contracts, the mobile managersâ everyday life is characterized by a âpermanent provisionalityâ, that is, an incongruence of the initially imagined and the actual time horizons of their mobility. This article shows how this âpermanent provisionalityâ is worked into the material and social textures of expatriate homes.

3D-Druck - Eine Technologie als Schlüssel zur Steigerung der Teilhabe - Kruse, Anne; Ott, Manuel; Risse, Lena; Koch, Rainer

Experimental failure analysis of adhesively bonded steel/CFRP joints under quasi-static and cyclic tensile-shear and peel loading - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (International Journal of Adhesion and Adhesives)
Keywords: Epoxy adhesive; fatigue strength; shear; peel; Steel-CFRP joints

Homotopic approach for turnpike and singularly perturbed optimal control problems - Cots, Olivier; Gergaud, Joseph; Wembe Moafo, Boris Edgar (ESAIM: Proceedings and Surveys)
The first aim of this article is to present the link between the turnpike property and the singular perturbations theory: the first one being a particular case of the second one. Then, thanks to this link, we set up a new framework based on continuation methods for the resolution of singularly perturbed optimal control problems. We consider first the turnpike case, then, we generalize the approach to general control problems with singular perturbations (that is with fast but also slow variables). We illustrate each step with an example.
Keywords: Immunology

Brand names as multimodal constructions. On the role of typography as an additional indicator of onymisation. - Dübbert, Alexander (Linguistics Vanguard)
Brand names are a common part of the everyday consumer environment, and can be found on countless visual surfaces such as food packaging. A key characteristic of brand names is their fixed design. Many brand names owe their linguistic form to units that originally did not constitute proper names. They developed into brand names through complex sub-processes of what is commonly referred to as onymisation. These processes include semantic, morphological and phonological/graphemic changes. The aim of this paper is to explore how the specific typographic design of a brand name can be an additional indicator in its process of onymisation. After clarifying the concepts of onymisation and typographic design, an extended multimodal construction model is presented. The basis of the paper is an analysis of a corpus of image data comprising more than 600 photographs of food packaging. In order to get a first impression of how the multimodal constructions of brand names could look, an omission test following a suggestion by Ziem (2017) is applied to the data.

Geometric and Numerical Methods in Optimal Control and Zermelo Problems on Revolution Surfaces - Applications - Wembe Moafo, Boris Edgar

Sozialpädagogische Qualifizierungen weiterdenken - Göddertz, Nina (Sozial Extra)
Viele Wege führen in die sozialpädagogische Praxis, doch nach wie vor stellt sich die Frage, wie sozialpädagogisches Handeln gelernt und gelehrt werden kann. Unter Bezugnahme auf kritisch bildungstheoretisch-fundierte Ansätze plädiert der Beitrag für eine Weiterentwicklung einer kritischen Didaktik der beruflichen Fachrichtung Sozialpädagogik.
Keywords: Fachdidaktik Sozialpädagogik Kritische Bildungstheorie Emanzipation und Mündigkeit

Concept development of a method for identifying friction coefficients for the numerical simulation of clinching processes - Böhnke, Max; Rossel, Moritz Sebastian; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (The International Journal of Advanced Manufacturing Technology)
Abstract In order to reduce fuel consumption and thus pollutant emissions, the automotive industry is increasingly developing lightweight construction concepts that are accompanied by an increasing usage of aluminum materials. Due to poor weldability of aluminum in combination with other materials, mechanical joining methods such as clinching were developed and established in series production. In order to predict the relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard, the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals as well as between the sheet metal and clinching tools has a significant impact on the geometrical formation of the clinched joint. No testing methods exist that can sufficiently investigate the frictional behavior in sheet materials, especially under high interface pressures, different relative velocities, and long friction paths, while allowing a decoupled consideration of the test parameters. This paper describes the development of further testing concepts based on a proven tribo-torsion test method for determining friction coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum and steel sheet material in clinching processes is investigated using numerical simulation. Based on these findings, the developed concepts focus on determining friction coefficients at interface pressures of the above materials, yield stress, as well as the reproduction of the occurring friction conditions between sheet metal materials and tool surfaces in clinching processes using tool substitutes. Furthermore, wear investigations between sheet metal material and tool surface were carried out in the friction tests with subsequent EDX analyses of the frictioned tool surfaces. The developed method also allows an optical deformation measurement of the sheet metal material specimen by means of digital image correlation (DIC). Based on a methodological approach, the test setups and the test systems used are explained, and the functionality of the concepts is proven by experimental tests using different sheet metal materials.

Concept development of a method for identifying friction coefficients for the numerical simulation of clinching processes - Böhnke, Max; Rossel, Moritz; Bielak, Christian R.; Bobbert, Mathias; Meschut, Gerson (The International Journal of Advanced Manufacturing Technology)
Abstract In order to reduce fuel consumption and thus pollutant emissions, the automotive industry is increasingly developing lightweight construction concepts that are accompanied by an increasing usage of aluminum materials. Due to poor weldability of aluminum in combination with other materials, mechanical joining methods such as clinching were developed and established in series production. In order to predict the relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard, the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals as well as between the sheet metal and clinching tools has a significant impact on the geometrical formation of the clinched joint. No testing methods exist that can sufficiently investigate the frictional behavior in sheet materials, especially under high interface pressures, different relative velocities, and long friction paths, while allowing a decoupled consideration of the test parameters. This paper describes the development of further testing concepts based on a proven tribo-torsion test method for determining friction coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum and steel sheet material in clinching processes is investigated using numerical simulation. Based on these findings, the developed concepts focus on determining friction coefficients at interface pressures of the above materials, yield stress, as well as the reproduction of the occurring friction conditions between sheet metal materials and tool surfaces in clinching processes using tool substitutes. Furthermore, wear investigations between sheet metal material and tool surface were carried out in the friction tests with subsequent EDX analyses of the frictioned tool surfaces. The developed method also allows an optical deformation measurement of the sheet metal material specimen by means of digital image correlation (DIC). Based on a methodological approach, the test setups and the test systems used are explained, and the functionality of the concepts is proven by experimental tests using different sheet metal materials.

Deutschsprachige Oratorien des 'langen 19. Jahrhunderts' : Studien zu vergessenen Gattungsbeiträgen
Der vorliegende Band versammelt die Ergebnisse eines wissenschaftlich-künstlerischen Lehrprojekts. Im Rahmen von zwei Seminaren, die an der Folkwang Universität der Künste in Essen sowie der Westfälischen Wilhelms-Universität Münster stattgefunden haben, haben sich Studierende im Sommersemester 2019 vergessenen deutschsprachigen Oratorien des »langen 19. Jahrhunderts« zugewandt und zu jeweils einem Werk einen eigenen Forschungsbeitrag verfasst. Ergänzt werden die acht Werkstudien um einen einführenden Beitrag aus theologisch-bibelwissenschaftlicher Perspektive.

MiDeCon: Unsupervised and Accurate Fingerprint and Minutia Quality Assessment based on Minutia Detection Confidence - Terhörst, Philipp; Boller, André; Damer, Naser; Kirchbuchner, Florian; Kuijper, Arjan (International IEEE Joint Conference on Biometrics, IJCB 2021, Shenzhen, China, August 4-7, 2021)

Privacy-Enhancing Face Biometrics: A Comprehensive Survey - Meden, Blaz; Rot, Peter; Terhörst, Philipp; Damer, Naser; Kuijper, Arjan; Scheirer, Walter J.; Ross, Arun; Peer, Peter; Struc, Vitomir (IEEE Trans. Inf. Forensics Secur.)

MAAD-Face: A Massively Annotated Attribute Dataset for Face Images - Terhörst, Philipp; Fährmann, Daniel; Kolf, Jan Niklas; Damer, Naser; Kirchbuchner, Florian; Kuijper, Arjan (IEEE Trans. Inf. Forensics Secur.)

Mitigating Soft-Biometric Driven Bias and Privacy Concerns in Face Recognition Systems - Terhörst, Philipp

On Soft-Biometric Information Stored in Biometric Face Embeddings - Terhörst, Philipp; Fährmann, Daniel; Damer, Naser; Kirchbuchner, Florian; Kuijper, Arjan (IEEE Trans. Biom. Behav. Identity Sci.)

PROJECT FOR THE DEVELOPMENT OF OPERATIONAL AND DEMAND-ORIENTED FIREFIGHTING EQUIPMENT - Hanses, Hendrik; Horwath, Ilona (Book of Abstracts 37th Danubia Adria Symposium on Advances in Experimental Mechanics)

Longitudinal mechanical joining of extruded aluminium profiles with increased tightness requirements - Neumann, Stefan; Meschut, Gerson; Kneuper, Florian; Hering, Oliver; Tekkaya, Erman

Herrscherhuldigung und Friedenslob – Das Opusculum cantionum des Johannes Flamingus (1571) - Höink, Dominik (Religiöse Friedensmusik von der Antike bis zur Gegenwart)